Editorial - Ejdus, Filip; Kovačević, Marko; Vujinović, Nikola (Journal of Regional Security, 2012)
Six years ago, the Western Balkans Security Observer was established as an academic journal of the Centre for Civil-Military Relations. Since then, the Journal has quickly developed from an in-house periodical into an academic publication covering security issues across the Western Balkans and South East Europe. As a confirmation of the improvement in quality, the Ministry of Education and Science of Serbia placed it on its list of academic journals in 2009. In the meantime, both the activities of the Centre and the topics covered by the Journal expanded beyond what their respective names indicated. As the Centre moved beyond civil-military relations to include wider area of security studies, it was renamed in 2010 into the Belgrade Centre for Security Policy. The Journal also widened its scope, not so much thematically but rather geographically. Increasingly, the number of submitted articles dealt with regions outside of the Western Balkans and the editorial board was not capable of properly accommodating them. Additionally, the Journal is faced with another problem. As one country after another joins the EU and NATO the Western Balkan region is actually shrinking as a security complex. As a result, the journal is faced with politically fortunate but analytically dangerous loss of its object of analysis. In order to ensure survival, the Journal decided to enlarge its geographic focus but keep its interest in regional level of analysis. Such transformation necessitated the adoption of the name – the Journal of Regional Security (JRS).